Leishmaniasis in Spain. Years 2019, 2020 y 2021 (Boletín Epidemiológico Semanal, 2023)
Introduction: leishmaniasis is an endemic zoonotic disease in Spain, where is caused by Leishmania infantum and transmitted by Phlebothomus. It can clinically present in humans as cutaneous leishmaniasis (CL), mucocutaneous (MCL) or visceral (VL). The aim of the study was to know the epidemiologic situation on human leishmaniasis in Spain from 2019 to 2021.Method: Epidemiologic descriptive analysis of human Leishmania cases notified to the Spanish Surveillance System from 2019 to 2021. Sociodemographic (age, sex, place of residence), clinical (category, hospitalization, dead, date of onset) and exposition (place) variables were analysed. Temporal trend from 2016 was also described and the information from both triennium (2019-2021 vs. 2016-2018) was compared.Results: there were 1,074 notified cases, out of which 1,041 were autochthonous. The trend of incidence rate (IR) of autochthonous cases from 2016 to 2019 was stable, with a marked reduction in 2020. The higher IR corresponded to Valencian Region and Balearic Islands, both for 2019-2021 and 2016-2018. Among cases, 65,7% were men with higher rates for the whole period. The higher IR were in children under 1 year old and those from 1-4. The clinical category was LV in 48,6% of cases, with differences in distribution (%) between regions. The proportion of hospital admission was 49,6%, being higher for LV (92,2%) and the case fatality rate was 1,9%. There were 33 imported cases, 45,5% corresponded to children under 15 years old, from the Maghreb. The missing values proportion exceeded 20% in some variables. Conclusions: the trend has been stable in the last years, with lower rates during pandemic years. Leishmaniasis is distributed throughout all the territory, with higher risk areas along the Mediterranean. The risk groups vary depending on age group and sex. There is room for improvement in the completion and availability of variables.
Keywords: leishmaniasis; Spain; epidemiological surveillance